A process for the production of weatherable flame-retardant ultrahigh molecular weight polypropylene melt blown biaxially oriented film

CN122723965APending Publication Date: 2026-09-11NINGBO RUICHENG PACKING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510280625.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2026-09-11

AI Technical Summary

Technical Problem

然而,这些方法往往需要在保证材料性能的同时,兼顾成本、加工难度和等方面的要求,因此在实际应用中仍存在一定的局限性和挑战

Benefits of technology

[0010]The beneficial effects of this invention are as follows: The addition of PBT to the outer layer enhances the flexibility of the PBT molecular chain, resulting in excellent thermal and mechanical properties. PBT exhibits high hardness and rigidity, significantly impacting the rigidity of the blend. Even a small amount of PBT can significantly improve the elastic modulus and rigidity of PP. When subjected to external tensile force, PBT particles can act as partial stress points, thereby increasing tensile strength. The ethylene segments in the maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer are compatible with PP, while the styrene segments are compatible with PBT, forming physical entanglement between components. This increases the notched impact strength of the blend. The reaction between the MAH groups grafted onto SEBS and the terminal carboxyl groups of PBT enhances the compatibilization effect, resulting in a strong interaction between PBT and the PP matrix. This strong interaction also makes the high heat distortion resistance of PBT more effective, thereby improving the heat resistance of PP.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a method for producing a weather-resistant and flame-retardant ultra-high molecular weight polypropylene melt biaxially stretched film. The ultra-high molecular weight polypropylene melt biaxially stretched film includes an outer layer, a middle layer, and an inner layer. The outer layer is composed of PP, piperazine pyrophosphate, chitosan, PBT, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer, polyglycolic acid, carbon nanotube-grafted glycidyl methacrylate hybrid particles, polypropylene-grafted maleic anhydride, and an antioxidant. The middle layer is composed of UHMWPP, PP, magnesium aluminum carbonate-type hydrotalcite, ethylene-acrylic acid copolymer, surface-modified tea powder, surface-modified nano-titanium dioxide, and ammonium polyphosphate. The inner layer is composed of PP, surface-modified calcined kaolin, surface-modified mica powder, lignin, LLDPE, POE, and an antioxidant. This invention exhibits good weather resistance and flame retardancy, as well as good thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of BOPP film technology, specifically a method for producing weather-resistant, flame-retardant, ultra-high molecular weight polypropylene melt biaxially stretched films. Background Technology

[0002] Ultra-high molecular weight polypropylene (UHMWPP), a propylene polymer with a molecular weight exceeding one million, has attracted widespread attention in recent years due to its excellent physical and chemical properties. However, despite its extraordinary strength, toughness, good tensile properties, and light transmittance, UHMWPP still faces some key technical challenges in practical applications, particularly in terms of weather resistance and thermal stability. To improve the weather resistance and thermal stability of UHMWPP, various modification methods and processing technologies have been explored. For example, adding additives such as antioxidants and UV absorbers can improve the material's weather resistance, while optimizing the polymerization process and adjusting the molecular weight distribution can enhance its thermal stability. However, these methods often require consideration of cost, processing difficulty, and other factors while ensuring material performance, thus presenting certain limitations and challenges in practical applications.

[0003] Therefore, developing a UHMWPP material with good weather resistance and thermal stability is of great significance for expanding its application areas and improving product performance. Summary of the Invention

[0004] In view of the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a method for producing weather-resistant and flame-retardant ultra-high molecular weight polypropylene melt bistretched film.

[0005] To solve the above problems, the technical solution of the present invention is: a method for producing a weather-resistant and flame-retardant ultra-high molecular weight polypropylene melt biaxially stretched film, wherein the ultra-high molecular weight polypropylene melt biaxially stretched film comprises an outer layer, a middle layer and an inner layer; The outer layer is composed of PP, piperazine pyrophosphate, chitosan, PBT, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer, polyglycolic acid, carbon nanotube-grafted polyglycidyl methacrylate hybrid particles, polypropylene-grafted maleic anhydride, and antioxidants. The intermediate layer is composed of UHMWPP, PP, magnesium aluminum carbonate type hydrotalcite, ethylene-acrylic acid copolymer, surface-modified tea powder, surface-modified nano titanium dioxide, and ammonium polyphosphate; The inner layer is composed of PP, surface-modified calcined kaolin, surface-modified mica powder, lignin, LLDPE, POE, and antioxidants; The production method includes the following steps: (1) The outer layer, middle layer and inner layer raw materials are blended separately and then sent to their respective extruders for melt mixing and plasticizing; (2) The molten melt is fed into the die head separately. After the melt merges in the die head, it forms a molten sheet through the flat die head opening. (3) The sheet is attached to the cooling roller with an air knife and rapidly cooled to form an unshaped sheet. Then, after cooling in a water bath, the sheet is shaped to form a cast sheet. (4) The cast sheet is stretched to form a thin film; (5) Wind up the film.

[0006] Further, the preparation method of carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles is as follows: hydroxylated carbon nanotubes are ultrasonically dispersed in xylene to obtain a uniform black dispersion. γ-aminopropyltrimethoxysilane is added to the dispersion, and the mixture is refluxed for 12 hours. After centrifugation, the black precipitate is separated, washed with anhydrous ethanol, and vacuum dried at 60°C to constant weight to obtain aminated carbon nanotubes. Aminated carbon nanotubes, glycidyl methacrylate, and deionized water are added to a container and thoroughly mixed under ultrasonic vibration. Ammonium persulfate is added, nitrogen gas is introduced, and the container is sealed. An oxidation-reduction polymerization reaction is carried out at 60°C. After centrifugation, the solid is washed with tetrahydrofuran and vacuum dried at 60°C to obtain carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles.

[0007] Furthermore, the outer layer components are as follows by mass ratio: PP 55%, piperazine pyrophosphate 10%, chitosan 2%, PBT 10%, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer 7.5%, polyglycolic acid 10%, carbon nanotube-grafted polyglycidyl methacrylate hybrid particles 2.5%, polypropylene-grafted maleic anhydride 2.5%, and antioxidant 0.5%.

[0008] Furthermore, the components of the intermediate layer are as follows by mass ratio: UHMWPP 35%, PP 35%, magnesium aluminum carbonate hydrotalcite 3%, ethylene-acrylic acid copolymer 12.5%, surface-modified tea powder 5%, surface-modified nano titanium dioxide 2%, and ammonium polyphosphate 7.5%.

[0009] Furthermore, the components of the inner layer are as follows by mass ratio: PP 59%, surface-modified calcined kaolin 5%, surface-modified mica powder 5%, lignin 15%, LLDPE 10%, POE 5%, and antioxidant 1%.

[0010] The beneficial effects of this invention are as follows: The addition of PBT to the outer layer enhances the flexibility of the PBT molecular chain, resulting in excellent thermal and mechanical properties. PBT exhibits high hardness and rigidity, significantly impacting the rigidity of the blend. Even a small amount of PBT can significantly improve the elastic modulus and rigidity of PP. When subjected to external tensile force, PBT particles can act as partial stress points, thereby increasing tensile strength. The ethylene segments in the maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer are compatible with PP, while the styrene segments are compatible with PBT, forming physical entanglement between components. This increases the notched impact strength of the blend. The reaction between the MAH groups grafted onto SEBS and the terminal carboxyl groups of PBT enhances the compatibilization effect, resulting in a strong interaction between PBT and the PP matrix. This strong interaction also makes the high heat distortion resistance of PBT more effective, thereby improving the heat resistance of PP. The outer layer of carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles, in conjunction with polypropylene-grafted maleic anhydride, can effectively compatibilize the PP / polyglycolic acid blend system. The degree of mutual influence between the crystallization processes of PP and polyglycolic acid increases. The addition of carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles improves the tensile strength and thermal stability of the composite material. The outer layer of piperazine pyrophosphate and chitosan has a synergistic flame retardant effect. Chitosan has a char-forming effect during combustion, which can prevent the composite material from further burning and decomposing. Adding chitosan is also beneficial to improving the thermal stability of the composite material. The addition of surface-modified tea powder in the middle layer can improve the tensile strength of the composite material. Surface-modified nano-titanium dioxide can also increase the tensile strength of the composite material. Surface-modified nano-titanium dioxide can enhance the weather resistance of the composite material. Surface-modified nano-titanium dioxide and ammonium polyphosphate have a synergistic flame retardant effect. The hydrotalcite in the middle layer is in an intercalation-exfoliation state, which enhances the interaction force with the PP molecular chain segments and improves the thermal stability of the composite material. The addition of inner layer modified calcined kaolin and modified mica improves the impact strength of PP; The inner layer contains lignin. In existing technologies, lignin is usually burned as fuel, which wastes resources and pollutes the environment. Filling PP with lignin can make use of resources. The addition of lignin can also improve the tensile strength and impact strength of the composite material. The interfacial adhesion between mica and PP matrix is ​​relatively small. The addition of mica reduces the compatibility of the mixed system and reduces toughness, thus reducing tensile strength. The addition of lignin makes up for this shortcoming. The addition of LLDPE and POE in the inner layer can improve the interfacial bonding between LLDPE and PP, thereby significantly improving the impact performance of PP and achieving a good toughening effect. Detailed Implementation

[0011] To provide a more intuitive and complete understanding of the technical solution of this invention, the following non-limiting features are described: A method for producing a weather-resistant and flame-retardant ultra-high molecular weight polypropylene melt biaxially stretched film, wherein the ultra-high molecular weight polypropylene melt biaxially stretched film comprises an outer layer, a middle layer, and an inner layer; The outer layer is composed of PP, piperazine pyrophosphate, chitosan, PBT, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer, polyglycolic acid, carbon nanotube-grafted polyglycidyl methacrylate hybrid particles, polypropylene-grafted maleic anhydride, and antioxidants. The intermediate layer is composed of UHMWPP, PP, magnesium aluminum carbonate type hydrotalcite, ethylene-acrylic acid copolymer, surface-modified tea powder, surface-modified nano titanium dioxide, and ammonium polyphosphate; The inner layer is composed of PP, surface-modified calcined kaolin, surface-modified mica powder, lignin, LLDPE, POE, and antioxidants; The production method of ultra-high molecular weight polypropylene melt biaxially stretched film includes the following steps: (1) The outer layer, middle layer and inner layer raw materials are blended separately and then sent to their respective extruders for melt mixing and plasticizing; (2) The molten melt is fed into the die head separately. After the melt merges in the die head, it forms a molten sheet through the flat die head opening. (3) The sheet is attached to the cooling roller with an air knife and rapidly cooled to form an unshaped sheet. Then, after cooling in a water bath, the sheet is shaped to form a cast sheet. (4) The cast sheet is stretched to form a thin film; (5) Wind up the film.

[0012] The preparation method of carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles is as follows: hydroxylated carbon nanotubes are ultrasonically dispersed in xylene to obtain a uniform black dispersion. γ-aminopropyltrimethoxysilane is added to the dispersion, and the mixture is refluxed for 12 hours. After centrifugation, the black precipitate is separated, washed with anhydrous ethanol, and vacuum dried at 60°C to constant weight to obtain aminated carbon nanotubes. Aminated carbon nanotubes, glycidyl methacrylate, and deionized water are added to a container and thoroughly mixed under ultrasonic vibration. Ammonium persulfate is added, nitrogen gas is introduced, and the container is sealed. An oxidation-reduction polymerization reaction is carried out at 60°C. After centrifugation, the solid is washed with tetrahydrofuran and vacuum dried at 60°C to obtain carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles.

[0013] The outer layer components, by mass ratio, are: PP 55%, piperazine pyrophosphate 10%, chitosan 2%, PBT 10%, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer 7.5%, polyglycolic acid 10%, carbon nanotube-grafted polyglycidyl methacrylate hybrid particles 2.5%, polypropylene-grafted maleic anhydride 2.5%, and antioxidant 0.5%. The antioxidant is antioxidant 1010.

[0014] The intermediate layer consists of the following components by mass ratio: UHMWPP 35%, PP 35%, magnesium aluminum carbonate hydrotalcite 3%, ethylene-acrylic acid copolymer 12.5%, surface-modified tea powder 5%, surface-modified nano-titanium dioxide 2%, and ammonium polyphosphate 7.5%. The tea powder is black tea powder. Both the tea powder and nano-titanium dioxide are surface-modified using KH550 silane coupling agent.

[0015] The inner layer components, by mass ratio, are: PP 59%, surface-modified calcined kaolin 5%, surface-modified mica powder 5%, lignin 15%, LLDPE 10%, POE 5%, and antioxidant 1%. The calcined kaolin is surface-modified using sodium dodecylbenzenesulfonate, and the mica powder is surface-modified using KH570 coupling agent. The antioxidant is antioxidant 1010. The mica powder content is relatively high at 5% by mass. A small amount of flaky mica (1%-3%) would insert into the PP matrix molecular chains, hindering chain movement and hardening the matrix material, leading to decreased toughness. When the mica content reaches 5%, the flaky mica can transfer stress and induce more crazes, shear bands, and voiding effects. During fracture, it absorbs a large amount of deformation energy, improving the impact performance and fracture toughness of the composite material.

[0016] This invention incorporates PBT in the outer layer. PBT molecular chains are highly flexible and possess excellent thermal and mechanical properties. It exhibits high hardness and rigidity, significantly impacting the rigidity of the blend. Even a small amount of PBT can significantly improve the elastic modulus and rigidity of PP. When subjected to external tensile force, PBT particles can act as partial stress points, thereby increasing tensile strength. The ethylene segments in the maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer are compatible with PP, while the styrene segments are compatible with PBT, forming physical entanglement between components. This increases the notched impact strength of the blend. The MAH groups grafted onto SEBS react with the terminal carboxyl groups of PBT, enhancing the compatibilization effect and creating a strong interaction between PBT and the PP matrix. This strong interaction also makes the high heat distortion resistance of PBT more effective, thus improving the heat resistance of PP. The outer layer of carbon nanotube-grafted glycidyl methacrylate hybrid particles, in synergy with polypropylene-grafted maleic anhydride, effectively compatibilizes the PP / polyglycolic acid blend system, increasing the mutual influence between the crystallization processes of PP and polyglycolic acid. The addition of carbon nanotube-grafted glycidyl methacrylate hybrid particles improves the tensile strength and thermal stability of the composite material. The glycidyl methacrylate grafted onto the surface of the carbon nanotube-grafted glycidyl methacrylate hybrid particles contains a large number of epoxy-containing side chains, which can simultaneously undergo esterification reactions with both polypropylene-grafted maleic anhydride and polyglycolic acid, thereby forming a PP-carbon nanotube graft in the system. The poly(glycidyl methacrylate) hybrid particles-polyglycolic acid component enhances the interaction between the two phases. Under the synergistic compatibilizing effect of carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles and polypropylene-grafted maleic anhydride, the polyglycolic acid phase has a smaller dispersion size and enhanced interfacial interaction, which further enhances the reinforcing effect of the polyglycolic acid organic rigid particles. The carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles undergo esterification with polyglycolic acid and polypropylene-grafted maleic anhydride to form a network structure. The formation of the network structure can inhibit the thermal motion of macromolecular chains and the overflow of decomposition products, thereby delaying the thermal decomposition process. The outer layer of piperazine pyrophosphate and chitosan has a synergistic flame retardant effect. Chitosan has a char-forming effect during combustion, which can prevent the composite material from further burning and decomposing. Adding chitosan is also beneficial to improving the thermal stability of the composite material. Chitosan has a lot of reactive hydroxyl groups, and the release of phosphoric acid from piperazine pyrophosphate makes chitosan more effective in carbon formation, thereby inhibiting the thermal decomposition of PP and thus improving the thermal stability of the composite material. The addition of surface-modified tea powder to the intermediate layer can improve the tensile strength of the composite material. Surface-modified nano-titanium dioxide can also increase the tensile strength of the composite material and enhance its weather resistance. Surface-modified nano-titanium dioxide and ammonium polyphosphate have a synergistic flame-retardant effect. The -OH groups on the surface of rigid nano-titanium dioxide form hydrogen bonds with the -OH groups on the surface of tea powder, and the alkyl groups introduced by KH550 to the modified nano-titanium dioxide and tea powder are intertwined with the PP matrix, further increasing the rigidity of the composite material. During the aging process, lignin and polypropylene degrade, macromolecular chains break, and impact strength decreases. However, nano-titanium dioxide effectively reduces lignin degradation, thus slowing down the decrease in impact strength. Nano-titanium dioxide can inhibit the decrease in tensile strength during the aging process, thereby increasing the weather resistance of the material. During combustion, the nano-titanium dioxide migrates to the surface of the material to form a denser char layer, which hinders the transfer of heat and oxygen during combustion, thus slowing down the combustion rate. Ammonium polyphosphate produces PO and PO2 at high temperatures. Free radicals can slow down or terminate the free radical chain reaction, thereby playing a flame-retardant role. In addition, nano-titanium dioxide can promote the formation of char layer during the combustion process. When the free radicals such as PO and PO2 formed by ammonium polyphosphate delay its reaction, the char layer will also isolate the material from the contact with air. The two work together to reduce the combustion rate and achieve the flame-retardant effect. The intermediate layer of hydrotalcite is in an intercalation-exfoliation state, which enhances the interaction force with the PP molecular chain segments and improves the thermal stability of the composite material. The groups in the ethylene-acrylic acid copolymer undergo a melt grafting reaction with the hydroxyl groups of the hydrotalcite, which can encapsulate the hydrotalcite. The molecular chains of the ethylene-acrylic acid copolymer are inserted between the hydrotalcite layers, which enhances the interaction force with the PP molecular chains, thereby improving the thermal stability of the composite material. The addition of inner-layer modified calcined kaolin and modified mica improves the impact strength of PP. The introduction of calcined kaolin has a heterogeneous nucleation effect on PP, reducing its spherulite size, which increases the impact strength of the composite system. The tensile strength is increased because the addition of modified calcined kaolin inhibits the movement of macromolecular chains. The inner layer incorporates lignin. In existing technologies, lignin is typically burned as fuel, resulting in resource waste and environmental pollution. Filling PP with lignin allows for resource utilization. The addition of lignin also improves the tensile and impact strength of the composite material. The interfacial adhesion between mica and the PP matrix is ​​relatively weak. The addition of mica reduces the compatibility and toughness of the mixed system, thus decreasing tensile strength. The addition of lignin compensates for this drawback. Lignin has a heterogeneous nucleation effect, which promotes the crystallization of PP material and increases the number of closely ordered molecules, thereby increasing tensile strength. As an organic rigid particle, lignin dispersed in the PP matrix easily yields and undergoes large plastic deformation under external force, thus absorbing a large amount of impact energy and improving the impact strength of the sample. The addition of LLDPE and POE in the inner layer can improve the interfacial bonding between LLDPE and PP, thereby significantly improving the impact performance of PP and achieving a good toughening effect.

Claims

1. A method for producing a weather-resistant, flame-retardant, ultra-high molecular weight polypropylene melt bistretched film, characterized in that: Ultra-high molecular weight polypropylene melt biaxially stretched film comprises an outer layer, a middle layer, and an inner layer; The outer layer is composed of PP, piperazine pyrophosphate, chitosan, PBT, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer, polyglycolic acid, carbon nanotube-grafted polyglycidyl methacrylate hybrid particles, polypropylene-grafted maleic anhydride, and antioxidants. The intermediate layer is composed of UHMWPP, PP, magnesium aluminum carbonate type hydrotalcite, ethylene-acrylic acid copolymer, surface-modified tea powder, surface-modified nano titanium dioxide, and ammonium polyphosphate; The inner layer is composed of PP, surface-modified calcined kaolin, surface-modified mica powder, lignin, LLDPE, POE, and antioxidants; The production method includes the following steps: (1) The outer layer, middle layer and inner layer raw materials are blended separately and then sent to their respective extruders for melt mixing and plasticizing; (2) The molten melt is fed into the die head separately. After the melt merges in the die head, it forms a molten sheet through the flat die head opening. (3) The sheet is attached to the cooling roller with an air knife and rapidly cooled to form an unshaped sheet. Then, after cooling in a water bath, the sheet is shaped to form a cast sheet. (4) The cast sheet is stretched to form a thin film; (5) Wind up the film.

2. The method for producing a weather-resistant, flame-retardant, ultra-high molecular weight polypropylene melt biaxially stretched film according to claim 1, characterized in that: The preparation method of carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles is as follows: hydroxylated carbon nanotubes are ultrasonically dispersed in xylene to obtain a uniform black dispersion. γ-aminopropyltrimethoxysilane is added to the dispersion, and the mixture is refluxed for 12 hours. After centrifugation, the black precipitate is separated, washed with anhydrous ethanol, and vacuum dried at 60°C to constant weight to obtain aminated carbon nanotubes. Aminated carbon nanotubes, glycidyl methacrylate, and deionized water are added to a container and thoroughly mixed under ultrasonic vibration. Ammonium persulfate is added, nitrogen gas is introduced, and the container is sealed. An oxidation-reduction polymerization reaction is carried out at 60°C. After centrifugation, the solid is washed with tetrahydrofuran and vacuum dried at 60°C to obtain carbon nanotube-grafted poly(glycidyl methacrylate) hybrid particles.

3. The method for producing a weather-resistant, flame-retardant, ultra-high molecular weight polypropylene melt biaxially stretched film according to claim 1, characterized in that: The outer layer consists of the following components by mass ratio: PP 55%, piperazine pyrophosphate 10%, chitosan 2%, PBT 10%, maleic anhydride-grafted hydrogenated styrene-butadiene block copolymer 7.5%, polyglycolic acid 10%, carbon nanotube-grafted polyglycidyl methacrylate hybrid particles 2.5%, polypropylene-grafted maleic anhydride 2.5%, and antioxidant 0.5%.

4. The method for producing a weather-resistant, flame-retardant, ultra-high molecular weight polypropylene melt biaxially stretched film according to claim 1, characterized in that: The components of the intermediate layer by mass ratio are: UHMWPP 35%, PP 35%, magnesium aluminum carbonate type hydrotalcite 3%, ethylene-acrylic acid copolymer 12.5%, surface-modified tea powder 5%, surface-modified nano titanium dioxide 2%, and ammonium polyphosphate 7.5%.

5. The method for producing a weather-resistant, flame-retardant, ultra-high molecular weight polypropylene melt biaxially stretched film according to claim 1, characterized in that: The inner layer consists of the following components by mass ratio: PP 59%, surface-modified calcined kaolin 5%, surface-modified mica powder 5%, lignin 15%, LLDPE 10%, POE 5%, and antioxidant 1%.